2020
DOI: 10.3390/atmos11060551
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Weather Types on Soil Erosion Rates in Vineyards at “Celler Del Roure” Experimental Research in Eastern Spain

Abstract: To understand soil erosion processes, it is vital to know how the weather types and atmospheric situations, and their distribution throughout the year, affect the soil erosion rates. This will allow for the development of efficient land management practices to mitigate water-induced soil losses. Vineyards are one of the cultivated areas susceptible to high soil erosion rates. However, there is a lack of studies that link weather types and atmospheric conditions to soil erosion responses in viticultural areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…The A+F, TL, and CD weather types typically occurred in oriental zones (the S zone and the D area). The eastern zone shows similar weather type frequencies to other researches relating rainfall and weather type reported in the East of Spain, including Valencia (Rodrigo et al 2020). With the exception of Sierra Nevada (N), where NE-E winds and CD weather type were dominant for any rainfall intensity type, there was no clearly dominant wind direction explaining the rainfall intensity in any zone, although we note that there were no cases involving NW-N or SW-W winds (except in the D area).…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nsupporting
confidence: 82%
“…The A+F, TL, and CD weather types typically occurred in oriental zones (the S zone and the D area). The eastern zone shows similar weather type frequencies to other researches relating rainfall and weather type reported in the East of Spain, including Valencia (Rodrigo et al 2020). With the exception of Sierra Nevada (N), where NE-E winds and CD weather type were dominant for any rainfall intensity type, there was no clearly dominant wind direction explaining the rainfall intensity in any zone, although we note that there were no cases involving NW-N or SW-W winds (except in the D area).…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nsupporting
confidence: 82%
“…The importance of the runoff event of high intensity is usually a consequence of specific weather types as Nadal-Romero et al (2014) found. At the study sites Rodrigo Comino et al (2020) found that 60% of the runoff is due to the East winds, the ones from the Mediterranean Sea that contribute to wet and warm air masses. González-Hidalgo et al (2013) used 1800 catchments to be found that the contribution of the suspended sediment load at continental scale was dominated by the 25-largest daily events that delivered 46-63 % of the load, and the 5-largest daily events 23-39 %.…”
Section: Paper Accepted Pre-print Versionmentioning
confidence: 94%